2018
DOI: 10.3389/fphar.2018.00434
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine, a Novel NOTCH3 Methylation Stimulator, Significantly Suppresses Lung Carcinogenesis in Vitro and in Vivo

Abstract: Lung cancer is a leading cause of cancer-related deaths worldwide. NOTCH3 signaling is mainly expressed in non-small cell lung carcinoma (NSCLC), and has been proposed as a therapeutic target of NSCLC. While, few agents for preventing or treating NSCLC via targeting NOTCH3 signaling are used in modern clinical practice. Evodiamine (EVO), an alkaloid derived from Euodiae Fructus, possesses low toxicity and has long been shown to exert anti-lung cancer activity. However, the underlying anti-lung cancer mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…In the present study, the effective anticancer activity of Evo, which may be mediated by BMP9 via the upregulation of HIF-1α to partly increase the activity of p53, was demonstrated in human colon cancer. It has been reported that Evo exhibits great anti-cancer activities in many types of cancer, such as tongue, breast, colon, prostate and lung cancer (9)(10)(11)(12)26,27). As far as colon cancer is concerned, the anticancer activity of Evo may be mediated by inactivating the NF-κB (9) or TGF-β1 (11), or activating the p53/p21/Rb pathway (12).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the effective anticancer activity of Evo, which may be mediated by BMP9 via the upregulation of HIF-1α to partly increase the activity of p53, was demonstrated in human colon cancer. It has been reported that Evo exhibits great anti-cancer activities in many types of cancer, such as tongue, breast, colon, prostate and lung cancer (9)(10)(11)(12)26,27). As far as colon cancer is concerned, the anticancer activity of Evo may be mediated by inactivating the NF-κB (9) or TGF-β1 (11), or activating the p53/p21/Rb pathway (12).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the proliferation inhibition in A549 cells was induced by evodiamine, which was linked with the ability of evodiamine to increase the expression of oncoprotein metadherin, promote oxidative injury, arrest the cell cycle, and regulate the tumor-associated genes expression by controlling protein kinase B/ nuclear factor-κB (AKT/NF-κB) and sonic hedgehog/GLI family zinc finger 1 (SHH/GLI1) pathways [ 30 , 31 ]. Su et al (2018) reported that evodiamine activate DNA methyltransferase 3A (DNMT3A)-induced neurogenic locus notch homolog protein 3 (NOTCH3) methylation, and subsequently induced growth inhibition in both A549 and H1299 NSCLC cells [ 32 ]. Moreover, the cytoprotective autophagy was induced by evodiamine in Lewis lung carcinoma (LLC) cells, and the combination of evodiamine with autophagy inhibitor therapy increased cell chemosensitivity [ 33 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…Evodia rutaecarpa Bentham is a traditional herbal medicine commonly used in Asia as an analgesic, anti-emetic, hemostatic, anti-hypertensive, and uterotonic agent [ 39 ]. Evodiamine, an active ingredient isolated from the fruit of Evodia rutaecarpa Bentham , has been well documented to inhibit the proliferation of various human cancer cells [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Previous study has shown that Evo could also change the morphology and decrease viability and proliferation of renal carcinoma cells [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evo inhibited growth of human colorectal carcinoma cells by increasing expression of Bax and p53 and decreasing expression of Bcl-2 [ 42 ]. Evo induced G2/M cell cycle arrest and decreased expression of CyclinB1 and cdc2 in lung cancer [ 16 ]. Evo also induced G2/M arrest and apoptosis in H446 and H1688 human small-cell lung cancer cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation